A Legal Analysis Of The Acquitting Verdict For Criminal Act Of Embasement Rice Sale Funds - Sherly Almaya; Syahranuddin, Syahranuddin; Lidya Ramadhani Hasibuan (Sean Institute, 2024)
Among several criminal acts related to wealth and property, there is a criminal act known as embezzlement, the crime of embezzlement as regulated in Book II (Two) of the Criminal Code, in Chapter XXIV, concerning Crimes Against Wealth and Property, in criminal acts there is a principle that the suspect is not considered guilty if no one can prove that he is guilty based on the principle of law, where in the case study of the court decision in case No. 276 / Pid.B / 2023 / PN Bnj. The formulation of the problem in this study is How is the Legal Regulation on the Crime of Embezzlement, How is the Criminal Accountability for the Perpetrators of the Crime of Embezzlement and How is the author's analysis of the legal evidence of the acquittal given by the judge in trying the case of embezzlement in court in the study of court decision No. 276/Pid.B/2023/PN Bnj. This research was conducted with a descriptive approach with a qualitative method with a type of normative juridical research based on secondary data sources taken from case studies of court decisions and laws with analysis using related legal materials. The results of this study obtained results in the form of knowledge related to the form of legal conception related to proving charges of embezzlement in court which were proven based on evidence in the form of invoices which were acts of default and included in the scope of money debts. In this case, the author found how the legal conception in proving charges of embezzlement in court influenced the results of the decision where in the chronology of the case in case No. 276/Pid.B/2023/PN Bnj in proving the elements in Article 372 of the Criminal Code related to the crime of embezzlement has been fulfilled and should be punished with a criminal penalty of a maximum imprisonment of 4 years and a maximum fine of Rp. 900 thousand but the judge sentenced him by considering Article 191 paragraph 2 of the Criminal Code by declaring the defendant free from all legal charges.